A theory of transactions privacy - Charles M. Kahn; James McAndrews; William Roberds (Federal Reserve Bank of Atlanta, 2000)
In this paper, we consider the costs and benefits of transactions privacy. In the environment we consider, privacy is the concealment of potentially useful information, but concealment also potentially bestows benefits. In some versions of the environment, the standard Coasian logic applies: given an unambiguous initial assignment of rights and sufficient flexibility in contracting, efficiency in information revelation will result. Coasian bargaining may be impeded, however, by either an inability to make certain commitments or by the presence of significant investments that must be made before the transaction occurs. In such cases, initial assignments of rights (for example, privacy laws) can have consequences for efficiency
Keywords: 330; Internet; Electronic commerce; Consumer protection; Privacy